Design of Integrated Hybrid Configuration of Modular Multilevel Converter and Marx Generator to Generate Complex Waveforms for Dielectric Testing of Grid Assets - Dhanashree Ashok Ganeshpure; Thiago Batista Soeiro; Mohamad Ghaffarian Niasar; Nitish Milind Kulkarni; Pavol Bauer; Peter Vaessen (IEEE Open Journal of the Industrial Electronics Society)
This article proposes a new configuration of a modular multilevel converter (MMC) and a Marx generator to generate fast-rising impulse waveforms. This new configuration improves the capabilities of the MMC-based high voltage arbitrary wave shape generator to generate fast-rising impulse since the MMC topology faces many inherent limitations. Similar to the conventional superimposed circuit of the ac transformer or dc rectifier circuit with the Marx generator, three hybrid circuits of MMC and the Marx generator are introduced, where the most optimal choice is made considering the practical aspects of testing, such as the size, cost, and preparation time. Then, a detailed analytical study is performed on the Marx generator circuit and the MMC circuit, and both circuits are coupled together to deliver a complete guideline on choosing various system parameters when the impulse wave shape and the load capacitor are given. The concept of this new hybrid configuration is demonstrated with a scaled-down prototype where the impulse with a rise time of 1 $μ$ s is superimposed on different arbitrary wave shapes. Similarly, the MATLAB-Simulink simulation model validates the proposed configuration for a $200 \,kV$ dc link voltage and 67 submodules with the desired impulse performance.